Studi Sifat Fisika Tanah Sawah Tadah Hujan dan Kebun Kelapa Dalam pada Lahan Pasang Surut Desa Sentebang Kabupaten Sambas - rini rini; Dr. Ir. U. Edi Suryadi, MP Dr. Ir. U. Edi Suryadi, MP; Ir. Rita Hayati, M.Si Ir. Rita Hayati, M.Si (Jurnal Sains Pertanian Equator, 2016)
This study was conducted to determine differences in soil physical properties relations in the rainfed areas and coconut groves in a tidal swamp land in the village of Sambas Regency Sentebang. Statistical analysis method used is the F test. The parameters observed soil texture , bulk density (g /cm3), total porosity(%), the water content of field capacity(% vol), stability of soil aggregates(%), the depth of sulfidic, salinity, drainage, the depth of the ground water level ground reaction and c – organic. Based on the results of soil texture with sand fraction in rainfed areas with a depth of 0-20 cm of sand content (0.63%) is smaller than the dust(41.62%) and clay(57.75%) is greater than the second , while the fraction of the land in rainfed areas with a depth of 20-40 cm sand fraction and dust smaller. Fraction of land in palm plantation land in the depths of 0- 20 cm higher fraction of sand, silt and clay than on the depth of 20-40 cm.Bobot contents showed that at a depth of 0-20 cm showed that soil bulk density rainfed significantly different soil bulk density results in a coconut plantation. Meanwhile, at a depth of 20-40 cm soil bulk density rainfed not significantly different from the weight of the contents of coconut groves and a depth of 0-20 cm in total porosity of rainfed land was not significantly different from the results of total porosity in the palm garden soil and at a depth of 20- 40 cm total porosity of rainfed significantly different from the total porosity in a coconut plantation. In the field capacity moisture content of rainfed land was not significantly different from the results of field capacity moisture content of coconut in good garden soil at a depth of 0-20 cm or 20-40 cm, and the soil aggregate stability at a depth of 0-20 cm soil rainfed not significantly different from the results of soil aggregate stability in a coconut plantation and at a depth of 20-40 cm soil stability rainfed significantly different from the stability of soil aggregates in a coconut plantation